Diversity and structure of ant communities associated with oak, pine, eucalyptus and arable habitats in Portugal - Cammell, M E; Way, M J; Paiva, M R (Insectes Sociaux, 1996)
In central Portugal, 28 species of ants were found in oak, 25 in pine, 35 in eucalyptus and 12 in arable habitats, a total of 43 species. They include five numerically dominant species, the exotic Argentine ant. Linepithema (Iridomyrmex) humile and four native species, Crematogaster scutel- laris, Pheidole pallidula, Tapinoma nigerrimum and Tetramorium hispanicum. L. humile occurred in 34 % of sampled sites. When present, it was abundant in all three arboreal habitats, where it was associated with strikingly decreased ant species richness and equitability. Such diversity was greater in L. humile - colonised arable habitats, where the ant was much less abundant than in the arboreal habitats. Where L. humile was absent, C. scutellaris and P pallidula were usually co-dominants in oak and pine, and T. nigerrimum and T. hispanicum in the arable habitat, but all were absent or rare in eucalyptus. Ants were numerically least abundant in eucalyptus but, in the absence of L. humile, species richness was greater and the community more equitable than in the other habitats. L. humile - absent arable habitats supported the poorest and least equitable ant community.
Keywords: Ants; community ecology; diversity; Dominance; Linepithema humile; Portugal.